Analysis of Government Responsibility in Enforcing the Rules of Riverbanks (Case Study: Bringin Riverbanks, Wonosari Village, Ngaliyan Sub-district, Semarang City) - Nadia Salsabila (Faculty of Law, Universitas Negeri Semarang, 2025)
This research aims to analyze the factors that cause violations of the Bringin River boundary in Wonosari Village, Ngaliyan Subdistrict, Semarang City, and examine the implementation of government responsibilities, especially BBWS Pemali Juana in enforcing river boundary regulations. The research method used is a qualitative approach with empirical juridical research and data collection techniques through interviews, observations, and document studies. The results showed that river boundary violations were caused by several main factors, including: historical factors and land heritage, legality of land rights, socio-economic conditions of the community, lack of socialization and understanding of the law, limited land, and weak supervision and enforcement of regulations. The implementation of government responsibility in this case has not been running optimally. BBWS Pemali Juana as a technical agency is only limited to collecting data, identification, and limited socialization without being continued with strict enforcement, due to budget constraints, and weak coordination between agencies. This study recommends the need for the preparation of SOPs for enforcement by BBWS Pemali Juana, strengthening institutional coordination, and massive legal education to the community so that law enforcement can be carried out effectively and sustainably.